A influência da taxa de câmbio sobre os fluxos de comércio exterior - Flavio Lyrio Carneiro (Instituto de Pesquisa Econômica Aplicada (IPEA), 2014)
– This study aims to examine the theoretical literature concerning exchange-rate and balance-of-payments determination, in order to investigate how an exchange rate change may affect one country's foreign trade flows. Therefore, we analyze the different categories of balance-of-payments models - the elasticities and absorption approaches, monetary and portfolio balance models, and the intertemporal optimization approach - aiming to identify the main transmission mechanisms by which the change in exchange rate levels can influence the behavior of external accounts, particularly exports and imports. It is possible to identify two main routes by which this interaction occurs: the relative prices effect (ie, the change in the real exchange rate, which influences the decisions of supply and demand in the economy, and decisions on imports and exports in particular), which depends on the sensitivity of imports and exports to the real exchange rate; and the direct effect on absorption, which operates mainly through the so called "real balance effect" - the reaction of agents to changes in their real money stock, which leads them to modify absorption (increase or decrease your expenses) to restore the real balances they wish to maintain.
Keywords: F31; F41; 330; exchange rates; balance of payments; foreign trade